CD11c+ and IRF8+ cell densities in rectal cancer biopsies predict outcomes of neoadjuvant chemoradiotherapy - Benita C. Y. Tse; Sarah Bergamin; Pascal Steffen; George Hruby; Nick Pavlakis; Stephen J. Clarke; Justin Evans; Alexander Engel; Andrew Kneebone; Mark P. Molloy (OncoImmunology)
Approximately 20% of locally advanced rectal cancer (LARC) patients treated preoperatively with chemoradiotherapy (CRT) achieve pathologically confirmed complete regression. However, there are no clinically implemented biomarkers measurable in biopsies that are predictive of tumor regression. Here, we conducted multiplexed immunophenotyping of rectal cancer diagnostic biopsies from 16 LARC patients treated preoperatively with CRT. We identified that patients with greater tumor regression had higher tumor infiltration of pan-T cells and IRF8+HLA-DR+ cells prior to CRT. High IRF8+HLA-DR+ cell density was further associated with prolonged disease-specific survival with 83% survival at 5 y compared to 28% in patients with low infiltration. Contrastingly, low CD11c+ myeloid cell infiltration prior to CRT was a putative biomarker associated with longer 3- and 5-y disease-free survival. The results demonstrate the potential use of rectal cancer diagnostic biopsies to measure IRF8+ HLA-DR+ cells as predictors of CRT-induced tumor regression and CD11c+ myeloid cells as predictors of LARC patient survival.